Hubungan Ketebalan Dinding Diafragma Dengan Keberhasilan Weaning pada Pasien Kritis di ICU RSUP Haji Adam Malik Medan - Muhamad Soleh; Andriamuri Primaputra Lubis; Achsanuddin Hanafie (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Introduction: Critically ill patients are at risk of developing persistent organ dysfunction that can deteriorate the patient's clinical outcome. This leads to patients in life-threatening conditions that require intensive care. Patients in the Intensive Care Unit (ICU) mostly require mechanical ventilation. Prolonged mechanical ventilation can cause a decrease in the contractile ability of the diaphragm along with diaphragmatic muscle atrophy. This is known as Ventilator Induced Diaphragm Dysfunction (VIDD). Diaphragm dysfunction remained a major cause of weaning difficulty or failure. Ultrasonography measurement of diaphragm function can be used to predict the outcome of weaning from mechanical ventilation. Methods: This study used a prospective observational study with a cross-sectional method. The total sample consisted of 36 critical patients on mechanical ventilators in the ICU who were planned for weaning. Patients were measured for diaphragm wall thickness fraction using ultrasonography. Result: In the diaphragm thickness fraction less than 30%, the successful weaning group was 3 people (8.3%), and failed weaning as many as seven people (27.8%); in the diaphragm thickness fraction greater than 30%, the successful weaning group was 24 people (66.7%) and failed weaning as many as two people (5.6%). The mean diaphragm thickness fraction in the successful weaning group was 40.77 ± 10.12, while in the weaning failure group, it was 24.50 ± 6.89. There is a relationship between diaphragm wall thickness as a predictor of successful weaning in critical patients in the ICU with a p-value = 0.001. Conclusion: Measurement of diaphragm wall thickness using ultrasonography can be used to predict weaning success in critically ill patients on ventilators in the ICU.